Measurements of top quark pair production differential cross sections in √ the all-hadronic decay chennel in pp collisions AT s=13 TEV using the atlas detector - Scornajenghi, Matteo; Carbone, Vincenzo; Tassi, Enrico (My University, 2019)
In this thesis, the measurements of the differential cross sections of top quark pair production in proton - proton collisions at a center of mass energy of p s = 13 TeV are presented. Data are collected at the LHC by the ATLAS detector during the 2015 and 2016 data-taking periods, corresponding to an integrated luminosity of L = 36:1 fb􀀀1. The top quark pair events are selected in the fully hadronic decay channel, resolved regime. The measurements are presented for several kinematics spectra and for observables sensitive to Initial and Final State Radiation. The measured spectra are corrected for detector effects and are compared to several theoretical Monte Carlo simulations. The measured spectra provide stringent tests of perturbative QCD, gives a better understanding of the top quark pair production mechanism and can be used to tune the Monte Carlo simulations. In addition, the expected performance of the Inner Tracker and the High Granularity Timing Detector, which will be installed during the Phase II upgrade of the ATLAS detector, will be presented
Dottorato di Ricerca in Scienze e Tecnologie Fisiche, Chimiche e dei Materiali. Ciclo XXXI
Keywords: Hadron interactions; Large hadron collider